Cannabis use is associated with alterations in NLRP3 inflammasome related gene expression in monocyte-derived macrophages from people living with HIV - Walter, Kyle C.; Avalos, Bryant; Ford, Mary K.; Laird, Anna E.; Boustani, Ali; Spencer, Matthew; Shu, Leeann; Chaillon, Antoine; Crescini, Melanie; Cookson, Debralee; Ellis, Ronald J.; Letendre, Scott L.; et al. (Frontiers in Immunology, 2025)
IntroductionHuman immunodeficiency virus (HIV) infection is often associated with chronic inflammation and cognitive dysfunction in people living with HIV (PWH). The nucleotide-binding oligomerization domain-like receptor containing pyrin domain 3 (NLRP3) inflammasome plays a crucial role in the secretion of pro-inflammatory cytokines, specifically interleukin (IL)-18 and IL-1β. Cannabis use and certain phytocannabinoids, such as cannabidiol (CBD), may provide therapeutic benefits in conditions associated with chronic inflammation.MethodsIn this cross-sectional study, we investigated the relationship between cannabis use and NLRP3-related gene expression in monocyte-derived macrophages (MDMs) from PWH (n = 43) and people without HIV (PWoH; n = 22). Participants were categorized as naïve, moderate, or daily cannabis users. Donor-derived MDMs were treated with CBD (30 μM), IL-1β (20 ng/mL), or CBD + IL-1β for 24 hours to examine effects on NLRP3-related gene expression. Gene expression data were analyzed using one-way and two-way ANOVA with Holm-Sidak’s multiple comparisons tests. Correlations between gene expression and clinical parameters were assessed using Pearson's correlation coefficient. Statistical significance was determined at p < 0.05.ResultsMDMs without treatment from PWH exhibited 83% higher NLRP3 mRNA expression compared to MDMs from PWoH. Furthermore, MDMs without treatment from moderate cannabis users expressed 61% less IL1β mRNA compared to naïve users, and MDMs from daily users expressed a 64% increase in IL18 expression compared to moderate users. Additionally, MDMs treated with CBD and IL-1β showed a 22% decrease in NLRP3 mRNA expression compared to IL-1β treated MDMs. When treated with CBD and IL-1β, we observed a significant increase in both IL1β (3-fold, p < 0.01) and IL18 (2-fold, p < 0.01) expression compared to vehicle. The relationship between NLRP3 mRNA expression in MDMs and global deficit scores in PWH not using cannabis was inverse to that relationship in PWH using cannabis.DiscussionOverall, these findings suggest that CBD, as consumed through cannabis use, may mitigate NLRP3 activation in PWH, potentially offering therapeutic benefits for chronic inflammation. However, the unexpected effects on downstream cytokine mRNA expression, combined with product heterogeneity, underscore the need for future mechanistic studies to fully delineate cannabinoid–inflammasome interactions in the context of HIV.